Educational outcomes of children from long-term foster care: Does foster parents' educational attainment matter?. (December 2019) - Berlin, Marie; Vinnerljung, Bo; Hjern, Anders; Brännström, Lars
Parental education is a robust predictor of children's educational outcomes in general population studies, yet little is known about the intergenerational transmission of educational outcomes in alternative family settings such as children growing up in foster care. Using Swedish longitudinal register data on 2.167 children with experience of long-term foster care, this study explores the hypothesized mediating role of foster parents' educational attainment on foster children's educational outcomes, here conceptualized as having poor school performance at age 15 and only primary education at age 26. Results from gender-stratified regression analyses suggest that there was an association between foster parental educational attainment and foster children's educational outcomes but that the educational transmission was weak and inconsistent and differed somewhat between males and females. For males, lower educational attainment in foster parents was associated with poor school performance but was not associated with educational attainment at age 26. The reverse pattern was found among females: the educational gradient was inconsistent for poor school performance but appeared in educational attainment. The results indicate that supported interventions for improving foster children's educational achievements are needed, even when placements are relatively stable and foster parents have a long formal education.